Social conventions : from language to law - Marmor, Andrei (Princeton monographs in philosophy., 2009)
Social conventions are those arbitrary rules and norms governing the countless behaviors all of us engage in every day without necessarily thinking about them, from shaking hands when greeting someone to driving on the right side of the road. In this book, Andrei Marmor offers a pathbreaking and comprehensive philosophical analysis of conventions and the roles they play in social life and practical reason, and in doing so challenges the dominant view of social conventions first laid out by David Lewis. Marmor begins by giving a general account of the nature of conventions, explaining the diffe.